2022
DOI: 10.3390/md20030209
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Venomics of C. flavidus and C. frigidus and Closely Related Vermivorous Cone Snails

Abstract: Cone snail venom biodiversity reflects dietary preference and predatory and defensive envenomation strategies across the ≈900 species of Conidae. To better understand the mechanisms of adaptive radiations in closely related species, we investigated the venom of two phylogenetically and spatially related species, C. flavidus and C. frigidus of the Virgiconus clade. Transcriptomic analysis revealed that the major superfamily profiles were conserved between the two species, including 68 shared conotoxin transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Another example is the work of Magdy et al (2023), where it was shown that the venom of Conus flavidus is at least two-fold more cytotoxic to the HepG2 cancer cell line than to a normal cell line. Joining this interesting work with the analysis of the transcriptome and proteome of this species described in Himaya et al (2022) could lead to the identification of novel candidates for drug discovery.…”
Section: Omics and Computational Approaches Highlight Organisms Of In...mentioning
confidence: 99%
“…Another example is the work of Magdy et al (2023), where it was shown that the venom of Conus flavidus is at least two-fold more cytotoxic to the HepG2 cancer cell line than to a normal cell line. Joining this interesting work with the analysis of the transcriptome and proteome of this species described in Himaya et al (2022) could lead to the identification of novel candidates for drug discovery.…”
Section: Omics and Computational Approaches Highlight Organisms Of In...mentioning
confidence: 99%